2010
DOI: 10.1116/1.3460343
|View full text |Cite
|
Sign up to set email alerts
|

Macromolecular depletion modulates the binding of red blood cells to activated endothelial cells

Abstract: Adhesion of red blood cells (RBCs) to endothelial cells (ECs) is usually insignificant but an enhanced adhesion has been observed in various diseases associated with vascular complications. This abnormal adhesion under pathological conditions such as sickle cell disease has been correlated with increased levels of various plasma proteins but the detailed underlying mechanism(s) remains unclear. Usually it is assumed that the proadhesive effects of plasma proteins originate from ligand interactions cross-linkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Additionally, the inner plasma membrane may translocate phosphatidylserine (PS) to the outer leaflet in the hyperglycemic microenvironment of DBC models. The translocated or "flipped" outer leaflet PS will contribute to the adherence of RBCs to the EC PS receptor, as well as to the EC matrix of thrombospondin, αvβ1, and CD36, which may add to the increased electron density of the proteinaceous electron-dense adhesion plaques of the RBC and EC [41,42]. Importantly, there were also adherent mononuclear white blood cells within the capillary lumen of NVUs observed in the cortical gray matter in DBC models, as depicted in previous figures ( Figures 4C,D, 7C and 8B), which will be discussed in greater detail as they relate to microglia remodeling.…”
Section: Imentioning
confidence: 99%
“…Additionally, the inner plasma membrane may translocate phosphatidylserine (PS) to the outer leaflet in the hyperglycemic microenvironment of DBC models. The translocated or "flipped" outer leaflet PS will contribute to the adherence of RBCs to the EC PS receptor, as well as to the EC matrix of thrombospondin, αvβ1, and CD36, which may add to the increased electron density of the proteinaceous electron-dense adhesion plaques of the RBC and EC [41,42]. Importantly, there were also adherent mononuclear white blood cells within the capillary lumen of NVUs observed in the cortical gray matter in DBC models, as depicted in previous figures ( Figures 4C,D, 7C and 8B), which will be discussed in greater detail as they relate to microglia remodeling.…”
Section: Imentioning
confidence: 99%
“…In fact, industrial applications of depletion flocculation are wide spread, including removing small particles from industrial waste by aggregating these particles, thus allowing mechanical separation from the fluid phase. However, this mechanism has only received minimal recognition in biological systems, even though the existence of depletion layers and the applicability of the depletion model to adhesive interactions of blood cells have been demonstrated in several recent studies [4,5,7,24,25,34,[43][44][45]47].…”
Section: Resultsmentioning
confidence: 99%
“…However, several findings that are more recent have shown that depletion interaction plays a major role in RBC-RBC interactions by providing the attractive force causing RBC come into close proximity and form aggregates [4,6,24,25]. Depletion-mediated forces are also a major determinant of RBC-EC adhesion in that they bring cells into close contact, thereby allowing or inducing the formation of stronger specific bonds [25,27,41,[43][44][45].…”
Section: The Conceptmentioning
confidence: 99%
See 1 more Smart Citation